APPLICATION OF DIGITAL TECHNOLOGIES IN ANALYSIS OF BIOMECHANICAL MOVEMENTS OF SWIMMERS - Allomov Erkinjon (Proximus Journal Publishing, 2025)
The article presents the theoretical and practical foundations of using modern digital technologies in the biomechanical analysis of swimmers. The main objective of the study is to evaluate swimming technique accuracy, efficiency, and energy economy through objective digital monitoring systems. The research used tools such as video analysis, 3D motion tracking, AI Motion Tracker, and smartwatches (Garmin Swim 2) to measure technical and physiological parameters. The obtained results allowed for the creation of individual biomechanical profiles and precise performance diagnostics for each swimmer. Analysis revealed that professional swimmers demonstrated shoulder rotation angles between 145°–156°, stroke length of 2.15–2.25 m, and SWOLF index values between 66–70, indicating high technical proficiency. Amateur swimmers showed shorter stroke length and higher stroke rate, which reduced energy efficiency. Artificial intelligencebased trajectory analysis identified technical errors with 94% accuracy. A strong negative correlation (r = – 0.78) was found between heart rate (HR) and stroke length (SL), confirming that higher technical proficiency reduces physiological strain. The study concludes that digital technologies provide a powerful framework for integrated biomechanical, physiological, and technical analysis in swimming. Implementing such systems in Uzbekistan can significantly improve training quality, digitize swimming sports, and enhance athletes' competitiveness at the international level.
Keywords: Swimming; biomechanics; digital technology; video analysis